Retrograde transarterial closure of small aneurysmal perimembranous ventricular septal defects using the amplatzer duct occluder II: a single-center mid-term analysis - Wang, Sibao; Luo, Gang; Ji, Zhixian; Pan, Silin (Frontiers in Cardiovascular Medicine, 2025)
BackgroundTranscatheter closure of aneurysmal perimembranous ventricular septal defects (pmVSDs) presents distinct anatomical challenges. While the retrograde transarterial approach using the Amplatzer Duct Occluder II (ADO II) has been described, data focusing on mid-term outcomes in this specific patient population remain limited.MethodsWe conducted a single-center, retrospective analysis of pediatric patients with hemodynamically significant small aneurysmal pmVSDs who underwent transcatheter closure via a retrograde approach with the ADO II device. Primary endpoints included procedural success, complications, and mid-term clinical and echocardiographic outcomes.ResultsTwenty-seven patients (median age 3.6 [3.0–4.6] years; median weight 15.9 [14.1–17.5] kg) were included. Defects had a median left ventricular inlet diameter of 4.0 [3.2–4.5] mm and right ventricular outlet diameter of 2.7 [2.5–3.1] mm; 59.3% were saccular aneurysms. The procedure was successful in 100% of cases using ADO II devices ranging from 4–4 to 6-6 mm. Median fluoroscopy time was 8.6 [8.1–12.1] min. No major procedural complications occurred. The immediate complete closure rate was 85.2%, rising to 100% at a median follow-up of 49 [28–72] months, with resolution of all clinical symptoms and no late device-related adverse events.ConclusionRetrograde transarterial closure of small aneurysmal pmVSDs with the ADO II device is a feasible, safe, and effective therapeutic strategy in appropriately selected pediatric patients.